2013
DOI: 10.1038/ejcn.2012.209
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lunch on children’s short-term cognitive functioning: a randomized crossover study

Abstract: In the first study on this topic lunch did not have relevant effects on children's cognitive functioning in the early afternoon. Future research needs to be done to figure out potential methodical and physiological explanations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 28 publications
2
18
2
Order By: Relevance
“…The present study revealed no evidence for a lunch-related improvement or decline of cognitive performance in schoolchildren in the early afternoon, about 90 min after finishing lunch. Although our previous studies CogniDo (11) and CogniDo PLUS (12) suggested slight improvements of single cognitive parameters shortly after lunch, the current study did not prove our hypothesis of potentially beneficial cognitive effects of lunch in the afternoon. Interestingly, the linear regression even indicated beneficial effects of lunch size as the individual change between lunch day and no lunch day decreased with larger lunch sizes for the parameter visual search letters.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The present study revealed no evidence for a lunch-related improvement or decline of cognitive performance in schoolchildren in the early afternoon, about 90 min after finishing lunch. Although our previous studies CogniDo (11) and CogniDo PLUS (12) suggested slight improvements of single cognitive parameters shortly after lunch, the current study did not prove our hypothesis of potentially beneficial cognitive effects of lunch in the afternoon. Interestingly, the linear regression even indicated beneficial effects of lunch size as the individual change between lunch day and no lunch day decreased with larger lunch sizes for the parameter visual search letters.…”
Section: Discussioncontrasting
confidence: 99%
“…It was not possible to obtain this information because of organisational reasons, but this question would be interesting for future studies. In the earlier CogniDo study (11) (n 105), the participants made significantly more omission errors in the tonic alertness task on the no lunch day compared with the lunch day (P = 0•03). The CogniDo PLUS study (12) (n 195) suggested slightly lower levels of false alarms in the task regarding working memory updating when lunch was eaten compared with the test condition in which lunch was omitted (P = 0•01)that is, after eating lunch, children responded less frequently to non-targets, to which they should not have responded.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The study design was integrated in the regular school-day routine and corresponded to the study schedule of the previous crossover study CogniDo 2 After completing these tests participants who had no lunch at the regular time received their lunch (14:00 p.m.).…”
Section: Study Schedulementioning
confidence: 99%
“…However, not all children eat breakfast and even if breakfast is consumed, the positive effects may not last, with a Swedish study reporting that 80% of schoolchildren were hungry an hour before lunch [8]. Although the consumption of a mid-morning snack may maintain or improve attention and academic performance throughout the morning, literature regarding the impact of snacks on cognition is very limited [9] and the meal effect may be different depending on whether a nightly rest or a working phase took place beforehand [10]. …”
Section: Introductionmentioning
confidence: 99%